Regulation of High Miscibility for Efficient Charge‐Transport in n‐Doped Conjugated Polymers. Issue 14 (16th February 2022) - Li, Qi‐Yi; Yao, Ze‐Fan; Wu, Hao‐Tian; Luo, Longfei; Ding, Yi‐Fan; Yang, Chi‐Yuan; Wang, Xin‐Yi; Shen, Zhihao; Wang, Jie‐Yu; Pei, Jian
Abstract: Strong interchain interactions of conjugated polymers usually result in poor miscibility with molecular dopants, limiting the doping efficiency because of uncontrolled phase separation. We have developed a strategy to achieve efficient charge‐transport and high doping miscibility in n‐doped conjugated polymers. We solve the miscibility issue through disorder side‐chains containing dopants better. Systemic structural characterization reveals a farther side‐chain branching point will lead to higher disorders, which provides appropriate sites to accommodate extrinsic molecular dopants without harming original chain packings and charge‐transport channels. Therefore, better sustainability of solid‐state microstructure is obtained, yielding a stable conductivity even when overloading massive dopants. This work highlights the importance of realizing high host‐dopant miscibility in molecular doping of conjugated polymers. Abstract : High host‐dopant miscibility and excellent carrier mobility can be simultaneously achieved in n‐doped conjugated polymers. High‐mobility polymers usually possess poor miscibility because of strong interchain interactions. Without harming the efficient charge‐transport based on the ordered polymer backbones packing, disordered side‐chains are introduced to accommodate dopants better without disturbing charge‐transport pathways.